Transnational Relationships and Cultural Identity of Older Migrants - Vanessa Burholt (GeroPsych, 2016)
We take a social identity approach to explore the associations between cultural heritage, social class, social support networks, transnational relationships and cultural identity. Data for 815 older people (≥ 55 years) from six ethnic groups living in England and Wales are used to help understand older migrants’ ethnic identity, cultural identity with the family’s country of origin and British identity. Regression models explain a low amount of variance. Different configurations of the independent variables - cultural heritage, social class, social support networks and transnational relationships (with children, siblings, other relatives) - predicted different forms of cultural identity. Transnational relationships provide migrants with a range of alternative identities into which they self-categorize or contrast to their group identity.